Combinatorial investigation of spin-orbit materials using spin Peltier effect. Issue 1 (December 2018) - Uchida, Ken-ichi; Sasaki, Michiko; Sakuraba, Yuya; Iguchi, Ryo; Daimon, Shunsuke; Saitoh, Eiji; Goto, Masahiro
Abstract Conversion between spin and charge currents is essential in spintronics, since it enables spin-orbit-torque magnetization switching, spin-current-driven thermoelectric generation, and nano-scale thermal energy control. To realize efficient spin-charge conversion, a variety of mechanisms, including spin Hall effects, Rashba-Edelstein effects, and spin-momentum locking in topological insulators, have been investigated and more comprehensive material exploration is necessary. Here we demonstrate high-throughput screening of spin-charge conversion materials by means of the spin Peltier effect (SPE). This is enabled by combining recently-developed SPE-imaging techniques with combinatorial materials science; using a composition-spread alloy film formed on a magnetic insulator, we observe the SPE-induced temperature change due to the spin Hall effect and obtain a continuous mapping of its composition dependence from the single sample. The distribution of the SPE signals reflects local spin-charge conversion capability in the alloy owing to unique heat-generation nature of the SPE. This combinatorial approach will accelerate materials research towards high-performance spintronic devices.